Assessment of the Diversity of Trees in Mt. Tapulao, Palauig, Zambales - Rivera, Nina Arra DJ.; Paz-Alberto, Annie Melinda (Silliman Journal, 2022)
This study focused on the assessment of the current status of the diversity of trees present in Mt. Tapulao, Palauig, Zambales. The assessment was limited to the identification of the trees present in the area, their conservation status, endemism, functions, and economic uses. Assessment and evaluation of the anthropogenic threats that may have an effect on ecological integrity were also conducted. Quadrat method method was used in the assessment of trees, with two quadrats designated in each five stations. Results revealed 77 species of trees present in the area with a diversity value of 3.77 based on Shannon’s Diversity Index. This value represents a very high diversity. Twenty three were identified at the species level, most of which were native to (57%) and endemic (43%) in the Philippines. The National List of Threatened Philippine Trees (DAO 2017-11) indicated that among the identified trees, six (6) species were under vulnerable conditions while some were endangered or critically endangered. According to the IUCN Red List, four (4) of the identified species were categorized as critically ,endangered, three (3) were vulnerable, two (2) were under the least concern category, and one (1) was an endangered species. Among the surveyed trees, majority were classified as forest trees (88.31%) while the rest were fruit trees (10.39%). Most (90.90%) of the fruit trees were utilized as a source of lumber for shelter. The forest ecosystem of Mt. Tapulao is experiencing anthropogenic threats. It was determined that the major threats were road construction, wildlife hunting, soil erosion or silt runoff, and tourism areas or recreational areas. Meanwhile, mining, solid waste, ecotourism, and quarrying indicated moderate impacts. The passage of ordinances and programs that aim to protect, conserve, and manage Mt. Tapulao’s resources played a key role in maintaining the biodiversity of the forest ecosystem. These ordinances and programs should be further implemented and improved in order to fully protect and conserve the ecological integrity of Mt. Tapulao.